Physical Activity and Sedentary Behavior of Children in Afterschool Programs: An Accelerometer-Based Analysis in Full-Day and Half-Day Elementary Schools in Germany - Kuritz, Arvid; Mall, Christoph; Schnitzius, Melina; Mess, Filip (Frontiers in Public Health, 2020)
Background: Regular physical activity (PA) and reduced sedentary behavior (SB) are positively related to children’s health and considered as pillars of a healthy lifestyle. Full-day schools with their after school programs (ASP) have an impact on children´s daily PA and SB. Studies investigating PA and SB in ASP which compare PA and SB between the organizational forms full-day and half-day school are rare. The aim of this study is to describe elementary school children’s PA and SB during ASP and compare the results to other time periods of the day, e.g. teaching hours and leisure time. Additionally, PA and SB of children in full-day and half-day schools are compared. Further, relevant factors influencing the achievement of the World Health Organization´s (WHO) PA guidelines for children, e.g. time spent in ASP, are investigated. Methods: PA and SB of 332 German students (n = 198 full-day; n = 134 half-day) from 11 different elementary schools was measured via accelerometry for five consecutive days within one school week in 2017. PA and SB during ASP and other times of the day were analyzed via one-way and factorial ANOVA, correlation and logistic regression. Results: Children attending full-day schools show the highest percentage of moderate to vigorous-PA (MVPA) (13.7%) and the lowest percentage of SB (49.5%) during ASP, in comparison to teaching hours and leisure time. In the afternoon hours, full-day school children show 20 minutes less SB than half-day school children. Children spending more time in ASP obtain significantly more SB (r = 0.23) and less MVPA (r = -0.15). Further, they less likely reach WHO’s PA guidelines (OR = 0.98). Conclusion: Peers and the choice as well as offer of extracurricular activities promote PA in ASP. Media availability leads to higher SB in leisure time. ASP help to be more active and less sedentary. Time spent in ASP should be limited, so that full-day school children still have the possibility to join other PA offers in leisure time. ASP time should contain a certain minimum amount of MVPA in line with ASP guidelines.